Pengembangan Media Pembelajaran Berbantu Wordwall Pada Materi Keberagaman Agama Untuk Siswa Kelas II Sekolah Dasar - Amanda, Mutia; Ramadan, Zaka Hadikusuma (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
The purpose of this study was to develop and test the feasibility of wordwall-assisted learning media on religious diversity material for grade II elementary school students. The formulation of the problem in this study is: how to develop wordwall learning media and how is the validity of wordwall learning media on religious diversity material for grade II elementary school students. This study uses a development research method with the ADDIE model, but only up to the development stage. This study uses a qualitative and quantitative approach, with data collection techniques in the form of interviews, validation questionnaires and teacher and student response questionnaires. The validation results show that this media is very feasible to use. Material validation obtained an average of 87.49%, language validation of 95.31%, and media validation of 90.33%. The overall average of the three aspects of expert validation obtained 91.04%, entering the very valid category. In addition, teacher responses obtained 90% while student responses obtained 94%. Thus, wordwall-assisted learning media is very feasible to use and effective in learning on religious diversity material in elementary schools.